Analisis Literasi Keuangan Mahasiswa di FKIP UNIS Tangerang - Agus Suherman; Esa Puspa Kartika Wardani; Khusaini Khusaini (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2020)
The purpose of this study was to determine the level of financial literacy in students and find out what factors influence financial literacy in students of Economic Education, Faculty of Teacher Training and Education, Islamic University of Syekh-Yusuf. This study uses descriptive analysis and the Multinominal Logit Test analysis method, with a sample of 116 taken using proportional random sampling in Economics Education students at the Faculty of Teacher Training and Education at the Islamic University of Syekh-Yusuf Tangerang by collecting data using a questionnaire.The results showed that the level of financial literacy of Economic Education students was in the moderate or sufficient category 63,8%. Besides the factors owned by students, namely GPA, education to fathers and parents' income have an influence on financial literacy. While other factors such as gender, class, place of residence, and mother's education level do not have an influence on financial literacy. DOI: https://dx.doi.org/10.17977/um014v13i12020p018